The Role of Modern Views and Concepts of Interethnic Relations in the System of the Social State (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article highlights the role of modern views and concepts of interethnic relations in the system of the welfare state. In addition, it was noted that the principles of the Social State are aimed at ensuring equal rights and opportunities for all citizens, regardless of nationality.